Parameterization of an Agent-Based Model of Spatial Distribution of Species - Bioco, João (2020)
Agent-based models (ABMs) have been widely applied in several fields such as ecology, biology, climate changes, engineering and many other fields. In ABMs approach, the behaviour of a system is determined by the local interactions between its individuals (agents), and the interactions between these individuals with the environment where they exist. Due to its interactions at the individual’s level, ABMs can produce quite realistic results regarding to the models behaviour. Therefore it is necessary to perform several analysis from the point of view of the models parametrization. In this paper we perform a parametric study in ways to analyze the implications of models parameterization in the models output, by implementing an agent-based model to simulate spatial distribution of species in an heterogeneous environment. The models output resulting from several parameters combination are compared and discussed.